An exploration of contextual dimensions impacting goals of care conversations in postgraduate medical education. Issue 1 (December 2016) - Roze des Ordons, Amanda; Lockyer, Jocelyn; Hartwick, Michael; Sarti, Aimee; Ajjawi, Rola
Abstract Background Postgraduate medical trainees are not well prepared difficult conversations about goals of care with patients and families in the acute care clinical setting. While contextual nuances within the workplace can impact communication, research to date has largely focused on individual communication skills. Our objective was to explore contextual factors that influence conversations between trainees and patients/families about goals of care in the acute care setting. Methods We conducted an exploratory qualitative study involving five focus groups with Internal Medicine trainees (n  = 20) and a series of interviews with clinical faculty (n  = 11) within a single Canadian centre. Thematic framework analysis was applied to categorize the data and identify themes and subthemes. Results Challenges and factors enabling goals of care conversations emerged within individual, interpersonal and system dimensions. Challenges included inadequate preparation for these conversations, disconnection between trainees, faculty and patients, policies around documentation, the structure of postgraduate medical education, and resource limitations; these challenges led to missed opportunities, uncertainty and emotional distress. Enabling factors were awareness of the importance of goals of care conversations, support in these discussions, collaboration with colleagues, and educational initiatives enabling skill development; these factors have resulted in learning, appreciation, and an established foundation for future educational initiatives. Conclusions Contextual factors impact how postgraduate medical trainees communicate with patients/families about goals of care. Attention to individual, interpersonal and system-related factors will be important in designing educational programs that help trainees develop the capacities needed for challenging conversations.